The Neuroprotective Efficiency of Cysteinyl Leukotriene Receptor Antagonist (Montelukast) in TBI; A Systematic Review and Meta-Analysis Protocol - Ayomide, Olobatoke Tunde; Kyaruzi, Victor Meza; Mugenyi, Nathan; Naeem, Ahmed; Shituluka, Musakanya; Ikwuegbuenyi, Chibuikem A; Oyesiji, Emmanuel; Elamin, Zobidah Yousif; David, Samuel Oreoluwa; Mduma, Emmanuel; Shimber, Emnet; Azouz, Heba Mohamed; et al. (Annals of Surgery Protocols, 2024)
Background: Traumatic Brain Injury (TBI) is one of the leading causes of morbidity, disability, and mortality across all ages, with a global annual incidence between 27 to 69 million. The pathophysiology of TBI involves the over-production of reactive oxygen species. This systematic review aims to evaluate the efficacy of montelukast in patients with TBI. Methodology: This systematic review aims to evaluate the neuroprotective efficacy of montelukast, a cysteinyl leukotriene receptor antagonist, in Traumatic Brain Injury (TBI) patients. The study will be conducted following the AMSTAR guidelines and reported according to PRIMA guidelines. A comprehensive literature search will be conducted in various databases, including Pubmed, Embase, Hinari, Cochrane Central Register of Controlled Trials, WHO International Clinical Trials Registry Platform, and clinicaltrials.gov, using keywords related to leukotriene receptor antagonists and TBI. The inclusion criteria for the studies will be randomized controlled trials in human subjects that compare montelukast with a placebo or montelukast with routine treatment. Two independent reviewers will screen the titles and abstracts of the studies identified by the search and obtain full-text articles for those that meet the inclusion criteria. The quality of the included studies will be evaluated using the Cochrane Risk of Bias tool or ROBIN. Data will be extracted from the studies using Eppi Reviewer or Microsoft Excel. A narrative synthesis of the data will be conducted, and a meta-analysis will be performed if appropriate. Ethics and dissemination: This research will utilize previously collected data, and no individuals will be involved. Therefore, obtaining ethical clearance is not required. The findings of this study will be presented at national and international conferences and submitted for publication in a journal undergoing peer review.
Keywords: Traumatic brain injury; Montelukast; Cysteinyl leukotriene receptor antagonist; Neuroprotection; Randomized controlled trial; Secondary data analysis; Meta-analysis; Leukotriene receptor antagonist; TBI; Cochrane risk of bias tool